Hubungan Manajemen Waktu dan Disiplin Kerja Terhadap Perilaku Prokrastinasi Pada Pegawai Dinas Pertanian Sumatera Utara - Hutabarat, Siti Lutfia; Atika, Atika; Tambunan, Khairina (Universitas Hamzanwadi, 2025)
Procrastination is a tendency to postpone work that can reduce productivity and work effectiveness, especially in government agencies that demand optimal performance and timely public services. High levels of procrastination among employees have the potential to hinder the achievement of organizational goals and reduce the quality of service to the public. This study aims to determine the effect of time management and work discipline on employee procrastination behavior at the UPTD PTPH-PMKP North Sumatra. This study uses a quantitative approach with a correlational method involving the entire population of 50 employees as respondents. A questionnaire was used to collect data, and multiple linear regression was used to examine it. The study found that work discipline had a big impact on avoiding putting things off, but time management did not. Simultaneously, time management and work discipline significantly influenced procrastination with a contribution of 41.9%. This finding indicates that improving work discipline is more effective in reducing the habit of procrastination than relying solely on time management skills.